Advances in biomedical applications of self-healing hydrogels. (21st April 2021) - Rammal, Hassan; GhavamiNejad, Amin; Erdem, Ahmet; Mbeleck, Rene; Nematollahi, Mohammad; Emir Diltemiz, Sibel; Alem, Halima; Darabi, Mohammad Ali; Ertas, Yavuz Nuri; Caterson, Edward J.; Ashammakhi, Nureddin
Abstract : In this paper, various self-healing hydrogels are discussed including their healing mechanisms and details of their current biomedical applications. Abstract : Hydrogels are important biomaterials that have several applications in drug and cell delivery, tissue engineering, three-dimensional (3D) printing and more recently, in sensing and actuating applications. With the advent of self-healing hydrogels, it is becoming possible to have smarter materials with sustainable mechanical properties under stress and also added functionalities. The mechanisms responsible for the self-healing behavior of these materials are related to their internal structure and processes triggered by damage they may sustain. These mechanisms rely on either chemical bonding or physical interactions of the structural components of hydrogels, or on both. Many self-healing hydrogels have been developed and tested in vitro and in animals. However, there are still challenges, especially with healing characteristics that need to be addressed and investigated in animal experiments before their clinical applications can be initiated, for which a multidisciplinary approach is required. In the current paper, various biomedical applications of self-healing hydrogels are discussed in detail, highlighting current challenges and future prospects.